Yield analysis optimization of microwave devices; antennas using non-linear partial-least-squares; polynomial chaos expansion - Klink, Dieter Gert (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD) -- Stellenbosch University, 2022.